A Convex Adaptive Total Variation Model Based on the Gray Level Indicator for Multiplicative Noise Removal. (5th June 2013) - Dong, Gang; Guo, Zhichang; Wu, Boying
Abstract : This paper focuses on the problem of multiplicative noise removal. Using a gray level indicator, we derive a new functional which consists of the adaptive total variation term and the global convex fidelity term. We prove the existence, uniqueness, and comparison principle of the minimizer for the variational problem. The existence, uniqueness, and long-time behavior of the associated evolution equation are established. Finally, experimental results illustrate the effectiveness of the model in multiplicative noise reduction. Different from the other methods, the parameters in the proposed algorithms are found dynamically.